Pembahasan Soal Tes Potensi Skolastik pada SBMPTN 2020 untuk Meningkatkan Kualitas Pelayanan Online di Tengah Pandemi Covid 19 di Bimbel dan Privat MATRIKS - Vivi Iswanti Nursyirwan; Nina Valentika; Choirul Basir; Gerry Sastro; Ilmadi Ilmadi (Indonesia Berdaya, 2020)
The purpose of community service carried out by the Pamulang University lecturer Team is to provide discussion assistance in answering questions about scholastic potential test to class XII high school students in preparing themselves to take part in the joint selection of state universities (SBMPTN) 2020. Partners in this community service are tutoring and private matrices in Pamulang, South Tangerang, Banten. The subject of community service is students in the public high school class XII who wish to enter state higher education through the SBMPTN 2020 test. The main problem faced by partners is that up to now Bimbel learning media has always been face to face and have never done online learning media, this because technologically Bimbel and private matrix not yet support in providing these services. The solution offered is to do online learning by online meeting application. The direct benefit of this dedication activity is an additional knowledge, skills in solving potential scholastic questions so that students can prepare for the joint selection of 2020 state universities with the method of solving problems quickly and easily. The derivate benefits are expected to be able to make students pass the SBMPTN 2020. This community service activity is carried out in the form of training by providing material and practice of completing the 2020 SBMPTN exam questions. The training is held for two weeks, namely in Monday to Friday, 11 -15  May 2020, and 18-22 May 2020. The method of activities used are practices, questions and answers and discussions. The analysis technique is done by observing aspects of student’s cognition and skills in conquering the subject matter.